Inhibitory coupling between inhibitory interneurons in the spinal cord dorsal horn - Ribeiro-; Bories Cyril; Lorenzo Louis-Etienne; Labrakakis Charalampos; De Koninck Yves (SAGE Publishing, 2009)
Abstract Local inhibitory interneurons in the dorsal horn play an important role in the control of excitability at the segmental level and thus determine how nociceptive information is relayed to higher structures. Regulation of inhibitory interneuron activity may therefore have critical consequences on pain perception. Indeed, disinhibition of dorsal horn neuronal networks disrupts the balance between excitation and inhibition and is believed to be a key mechanism underlying different forms of pain hypersensitivity and chronic pain states. In this context, studying the source and the synaptic properties of the inhibitory inputs that the inhibitory interneurons receive is important in order to predict the impact of drug action at the network level. To address this, we studied inhibitory synaptic transmission in lamina II inhibitory interneurons identified under visual guidance in spinal slices taken from transgenic mice expressing enhanced green fluorescent protein (EGFP) under the control of the GAD promoter. The majority of these cells fired tonically to a long depolarizing current pulse. Monosynaptically evoked inhibitory postsynaptic currents (eIPSCs) in these cells were mediated by both GABAA and glycine receptors. Consistent with this, both GABAA and glycine receptor-mediated miniature IPSCs were recorded in all of the cells. These inhibitory inputs originated at least in part from local lamina II interneurons as verified by simultaneous recordings from pairs of EGFP+ cells. These synapses appeared to have low release probability and displayed potentiation and asynchronous release upon repeated activation. In summary, we report on a previously unexamined component of the dorsal horn circuitry that likely constitutes an essential element of the fine tuning of nociception.